Metaxa2: improved identification and taxonomic classification of small and large subunit rRNA in metagenomic data. (23rd March 2015) - Bengtsson‐Palme, Johan; Hartmann, Martin; Eriksson, Karl Martin; Pal, Chandan; Thorell, Kaisa; Larsson, Dan Göran Joakim; Nilsson, Rolf Henrik
Abstract The ribosomal rRNA genes are widely used as genetic markers for taxonomic identification of microbes. Particularly the small subunit (SSU; 16S/18S) rRNA gene is frequently used for species‐ or genus‐level identification, but also the large subunit (LSU; 23S/28S) rRNA gene is employed in taxonomic assignment. The metaxa software tool is a popular utility for extracting partial rRNA sequences from large sequencing data sets and assigning them to an archaeal, bacterial, nuclear eukaryote, mitochondrial or chloroplast origin. This study describes a comprehensive update to metaxa – metaxa2 – that extends the capabilities of the tool, introducing support for the LSU rRNA gene, a greatly improved classifier allowing classification down to genus or species level, as well as enhanced support for short‐read (100 bp) and paired‐end sequences, among other changes. The performance of metaxa2 was compared to other commonly used taxonomic classifiers, showing that metaxa2 often outperforms previous methods in terms of making correct predictions while maintaining a low misclassification rate. metaxa2 is freely available from http://microbiology.se/software/metaxa2/.